Impact of Grinding and Sorting Particle Size on Phytochemical Yield in Dipterocarpus alatus Leaf Extract - Kritsadang Senawong; Somporn Katekaew; Suchat Juntahum; Kittipong Laloon (International Journal of Biomaterials)
The main objective of this study was to investigate the impact of grinding (pretreatment) with a pin mill on the crude extract yields of Dipterocarpus alatus (Yang-Na) leaves. A factorial design in a completely randomized design was conducted to study the combinational effects of sieve sizes (1.0, 1.5, and 3.0 mm) and feed rates (1.0, 1.5, and 3.0 kg min−1), examining the interaction of parameters for grinding oven-dried Yang-Na leaves. Ethanol extraction initially evaluated the influence of Yang-Na leaf powder with diverse particle sizes. When sorting particle size, the crude extract yield increased as the particle size decreased, with 0.038–0.150 mm particles yielding the highest extraction, although yields decline when the particle size is lower than 0.038 mm. The average particle sizes, production capacity, and fineness modulus all exhibited a significant decrease as the sieve size and feeding rate were reduced, while the specific energy consumption showed an inversely proportional relationship with these parameters. Intriguingly, the crude extract yield remained independent of the average particle size. Notably, the highest yield (14.79 g kg−1) was derived from a 0.31 mm average particle size, ground with a 1.5 mm sieve and a 3 kg min−1 feeding rate. This suggests that the pretreatment, involving both grinding conditions and sorting size, has an impact on the performance of the extraction process. However, this study offers an energy-efficient alternative, advocating for using average particle sizes without prior sorting, streamlining the extraction process while maintaining substantial yields. These insights underline the crucial influence of particle size and grinding techniques, advancing our understanding of efficient herbal extraction techniques for industrial applications.